Madeleine Leininger's Culture care diversity and universality theory - Leininger, Madeline (1988)
This paper is focused on the essential features of the nursing theory of cultural care diversity and universality. An overview of the essential features is discussed to show how the theory was developed and how it has evolved during the past three decades. The theory was initiated from clinical experiences recognizing that culture, a wholistic concept, was the missing link in nursing knowledge and practice. Through a creative process of concept explication, reformulation, and resynthesis, the the ory of cultural care was set forth as a guide for the development of nursing knowledge. The concept of culture was derived from anthropol ogy and the concept of care was derived from nursing. The theorist holds that cultural care provides the broadest and most important means to study, explain, and predict nursing knowledge and concomitant nursing care practice. The ultimate goal of the theory is to provide cultural congruent nursing care practices. The author contends that if one fully discovers care meanings, patterns, and processes, one can explain and predict health or well-being. The assumptions, definitions, and theoret ical explanations related to cultural care are presented with the sunrise model to depict the major components of the theory.